Nonlinear differential inequality - Hoang, N. S.; Ramm, Alexander G. (My University, 2011)
A nonlinear differential inequality is formulated in the paper. An estimate of the rate of growth/decay of solutions to this inequality is obtained. This inequality is of interest in a study of dynamical systems and nonlinear evolution equations in Banach spaces. It is applied to a study of global existence of solutions to nonlinear partial differential equations.
Keywords: Nonlinear inequality; Dynamical Systems Method (DSM); Stability